Teams in Small Organizations: Conceptual, Methodological, and Practical Considerations - Reiter-Palmon, Roni; Kennel, Victoria L.; Allen, Joseph A. (Frontiers in Psychology, 2021)
Research on teams and teamwork has flourished in the last few decades. Much of what we know about teams and teamwork comes from research using short-term student teams in the lab, teams in larger organizations, and, more recently, teams in rather unique and extreme environments. The context in which teams operate influences team composition, processes, and effectiveness. Small complex organizations are an understudied and often overlooked context that presents a rich opportunity to augment our understanding of teams and team dynamics. In this paper we discuss some of the ways in which teams and multi-team systems (teams of teams) in smaller organizations may differ from those found in larger organizations. Many of these differences present both practical and methodological challenges to the study of team composition and processes in small complex organizational settings. We advocate for the application and acceptance of new and less widely used methodological approaches to advance our understanding of the science of teams and teamwork in such contexts.